Biological effects of bergamot and its potential therapeutic use as an anti-inflammatory, antioxidant, and anticancer agent. (31st December 2023) - Adorisio, Sabrina; Muscari, Isabella; Fierabracci, Alessandra; Thi Thuy, Trinh; Marchetti, Maria Cristina; Ayroldi, Emira; Delfino, Domenico Vittorio
Abstract: Context: Bergamot, mainly produced in the Ionian coastal areas of Southern Italy (Calabria), has been used since 1700 for its balsamic and medicinal properties. Phytochemical profiling has confirmed that bergamot juices are rich in flavonoids, including flavone and flavanone glycosides which are responsible for its beneficial effects. Objective: Recently, it was shown that the combination of natural compounds with conventional treatments improves the efficacy of anticancer therapies. Natural compounds with anticancer properties attack cancerous cells without being toxic to healthy cells. Bergamot can induce cytotoxic and apoptotic effects and prevent cell proliferation in various cancer cells. Methods: In this review, the antiproliferative, pro-apoptotic, anti-inflammatory, and antioxidant effects of bergamot are described. Information was compiled from databases such as PubMed, Web of Science, and Google Scholar using the key words 'bergamot' accompanied by 'inflammation' and, 'cancer' for data published from 2015–2021. Results: In vitro and in vivo studies provided evidence that different forms of bergamot (extract, juice, essential oil, and polyphenolic fraction) can affect several mechanisms that lead to anti-proliferative and pro-apoptotic effects that decrease cell growth, as well as anti-inflammatory and antioxidant effects. Conclusions: Considering the effects of bergamot and its new formulations, we affirm the importance of its rational use in humans and illustrate how bergamot can be utilized in clinical applications. Numerous studies evaluated the effect of new bergamot formulations that can affect the absorption and, therefore, the final effects by altering the therapeutic profile of bergamot and enhancing the scientific knowledge of bergamot.